Realization of a complex-coupled InGaN/GaN-based optically pumped multiple-quantum-well distributed-feedback laser - Hofstetter, Daniel; Romano, Linda T.; Paoli, Thomas L.; Bour, David P.; Kneissl, Michael (My University, 2000)
We demonstrate an optically pumped complex-coupled InGaN/GaN-based multiple-quantum-well distributed-feedback laser in the violet/blue spectral region. The third-order grating providing feedback was defined holographically and dry etched through a portion of the active region by chemically assisted ion-beam etching. Epitaxial overgrowth of the GaN waveguide completed the device structure without introducing dislocations, as shown by transmission electron microscopy. The laser emitted light at 392.7 nm with high side-mode suppression and a narrow linewidth of 1.5 Å. In contrast to Fabry–Pérot lasers fabricated from the same piece of material, only a very minor change in emission wavelength was observed when operating the device at higher pump intensities.